Disinformation matters. The media-experts’ perspective on fake news, trust in media and counter strategies - Georgiadou, Vasiliki; Kafe, Anastasia; Kountouri, Fani (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2024)
The issue of disinformation is a growing concern, particularly due to the digital transformation of the public sphere and the media environment, compounded by the impact of COVID-19. This paper aims to explore various aspects of disinformation by analyzing interviews conducted with experts actively involved in either crea ting credible news or combating fake news during the pandemic. We introduce conceptual distinctions related to the phenomenon of disinformation and discuss the factors and actors involved in its spread during the COVID-19 era. Additionally, we highlight the impact of disinformation on the increasing distrust towards the media and propose counterstrategies for combating this issue.